Cónicas en las geometrías del taxista y euclidiana - Medina García de Correa, Nélida Salomé (2018)
To enhance the understanding of conics, we consider the circumference, ellipse, hyperbola in Euclidean geometry and cab geometry. Each conic is defined as a geometric locus, as a set of ordered pairs of real numbers satisfying an equation and as figures representing them in the plane in both Euclidean metric and taxicab driver metrics.